Comparative Study of Onion-like Carbons Prepared from Different Synthesis Routes towards Li-Ion Capacitor Application - Permana, Antonius Dimas Chandra; Ding, Ling; Gonzalez-Martinez, Ignacio Guillermo; Hantusch, Martin; Nielsch, Kornelius; Mikhailova, Daria; Omar, Ahmad (Batteries, 2022)
Li-ion capacitors (LIC) have emerged as a promising hybrid energy storage system in response to increasing energy demands. However, to achieve excellent LIC performance at high rates, along with cycling stability, an alternative anode to graphite is needed. Porous high-surface-area carbons, such as onion-like carbons (OLCs), have been recently found to hold high potential as high-rate-capable LIC anodes. However, a systematic understanding of their synthesis route and morphology is lacking. In this study, OLCs prepared from self-made metal organic frameworks (MOFs) Fe-BTC and Fe-MIL100 by a simple pyrolysis method were compared to OLCs obtained via high-temperature annealing of nanodiamonds. The LICs with OLCs produced from Fe-BTC achieved a maximum energy density of 243 Wh kg−1 and a power density of 20,149 W kg−1. Furthermore, excellent capacitance retention of 78% after 10,000 cycles was demonstrated. LICs with MOF-derived OLCs surpassed the energy and power density of LICs with nanodiamond-derived OLCs. We determined the impact of the MOF precursor structure and morphology on the resulting OLC properties, as well as on the electrochemical performance. Thus, MOF-derived OLCs offer significant potential toward high-performance anode material for LICs, enabling control over structure and morphology, as well as easy scalability for industrial implementation.
CRIS-Team Scopus Importer:2023-03-20
Keywords: high energy density; high power density; Li-ion capacitor; metal organic framework; onion-like carbon